Health benefits of seafood: A review of resources available to General Practitioners and Allied Health Professionals - McManus, Alexandra; Taylor, J.; Nicholson, Claire (Centre of Excellence Science Seafood & Health (CESSH), 2009)
This review focused on the collection and critical review of relevant resources that were available to General Practitioners (GPs) and Allied Health Professionals (AHPs) to use with patients as either a prevention or treatment measure for common lifestyle or medical conditions. All resources reviewed were in English and were designed to be used during a five to ten minute consultation. The identification process realised 120 current resources associated with the health benefits of regular consumption of seafood as part of a healthy diet that could be used by GPs and AHPs. The resource topics included arthritis (seven), cancer (six), dementia (one), dental health (two), diabetes (three), heart health (30), nutrition (40), osteoporosis (six) and preconception, pregnancy and breastfeeding (25). The critical review of resources revealed information about the format, target group, reference to seafood, credibility and suitability of the identified resources.The majority of identified resources (88.4%, n=106) were available electronically as either PDF files or webpages, a preferable, quick and easy mode of access for GPs and AHPs. Just over half (57.5%, n=69) of the identified resources were targeted at specific audiences. All of the resources made reference to the health benefits of regular consumption of fish (100%, n=120), 22.5% (n=27) made reference to seafood and 5% (n=6%) made reference to fish oil as part of a healthy diet. Only 15% (n=18) of the identified resources were suitable for use with the general Australian population at or below the recommended reading level of Year Eight. The majority (87.5%, n=105) of resources were found to be ‘credible’ or ‘highly credible’. Resources that were found to be ‘definitely not credible’, ‘not credible’ or ‘somewhat credible’ (12.5%, n=15) were primarily due to information being provided by commercial entities with possible competing interests. In summary, the most pertinent outcome from this research was that only 15% (n=18) of the resources reviewed were suitable for use with the general Australian population at the recommended reading level of Year Eight or lower.